PENERAPAN PENDEKATAN CTL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 013 BASILAM BARU DUMAI - Witri, Gustimal Witri; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The Rroblem to research This is result study match student of low class V SD Negeri 013 Basilam Baru. With average 60,5 with minimun completeness  criteria of 77 This metter for cause of least participant student in the studied process, because theacher still used lecture method. This research purpose to increase the result study match student to passed. Apply approach CTL to Student. Class V SDN 013 Basilam Baru Dumai. Teaching year 2013/2014. The problem formula in thethis research is “What the applied approach Contextual Teaching and Learning (CTL) can to increased the result study match student class V SDN 013 Basilam Baru ? This research did in the 2 siklus. In the process CTL, the student involved in active in the studied process, the student to exchange idea and opinion in the problem solving so the student can solved task in time. The research result to show like level studied of result match student class V SDN 013 Basilam Baru after made action like studied with applied CTL. This matter can to saw from average valve repetition day student. The result studied of student before action in categories of low average 60,5 where as the repetition daily siklus I 69,00 repetition daily siklus II with average 76,00 percentation of activity teacher. To siklus I is 64,28 % with good categorieds to increase to siklus II become 78,57 % with good categories. Percentation of activity student to siklus I is 57,14 % with categories enough increase to siklus II become 78,57% with good categories. Based on result the research and analysis data mentioned, can to make a knot that approach CTL can to increase the result study match student class V SDN 013 Basilam Baru Dumai. Keywords : The applied approach, CTL , Result Study Match